Power allocation between radar and jammer using conflict game theory - He, Bin; Yang, Ning (Electronics letters, 2024)
Conflict game theory is employed to analyze the countermeasure relationship between radar systems and jammers. To address this issue, a novel utility function and a Conflict Power Allocation Game (CPAG) algorithm are introduced for determining the Nash Equilibrium (NE) solution of the game. The utility function enables the calculation of optimal power response functions for both the radar system and the jammer, with the NE solution of the CPAG algorithm obtained through numerical computation. Simulation results demonstrate the convergence of the proposed CPAG algorithm to the NE solution, validating its efficacy. Finally, an analysis of the relationship between the utility function and pricing factors is conducted based on the proposed CPAG algorithm and simulation outcomes. This article introduces a novel utility function and a Conflict Power Allocation Game (CPAG) algorithm to analyze the countermeasure game dynamics between radar and jammer systems. By deriving optimal response functions using the utility function, the Nash Equilibrium (NE) solution of the game is calculated, demonstrating convergence of the CPAG algorithm. Simulation results validate the efficacy of the proposed approach, highlighting the relationship between the utility function and pricing factors.